(untitled) (The Pakistan Development Review, 1998)
From its inception the GATT had guided international trade most successfully until the early 1970s. However, afterwards the developed countries (DCs) increasingly recurred to new forms of trade restrictions not covered by the GATT rules. Ironically, these “grey measures” were mostly against the less developed countries (LDCs). These measures constrained international trade exactly at the time when the LDCs started penetrating developed markets. One of the main objectives of the Uruguay Round (UR) accord was to restrict the surge of protectionism. The accord was the most ambitious and detailed trade accord of all the GATT rounds. It established the World Trade Organisation (WTO). Before the UR accord the discrimination in textiles, clothing and agriculture was severe because tariffs and non-tariff barriers (NTBs) were employed in such a way that the overall effect of protection accumulated. The Round had agreed upon the harmonisation and reduction of tariffs, and elimination of NTBs (in stages) and thus it is expected that the effective protection will diminish in the DCs. The new accord has ensured multilateral rules for these sectors. All members expected that protection would be eventually lower with full implementation of the accord. In order to protect the interest of different groups the WTO has now lay down nondiscriminatory trading rules for services and trade-related aspects of intellectual property rights (TRIPs), thus covering all major fields of international trade policy.